A dual band meandered printed dipole antenna for RF energy harvesting applications - Sarma, Sanchari Sen; Akhtar, M. Jaleel (2016 IEEE 5th Asia-Pacific Conference on Antennas and Propagation (APCAP), 2016)
In this paper, a high gain printed dual-band meandered dipole antenna is proposed for RF energy harvesting applications in the GSM-1800 and WiFi (2.45 GHz) bands. The proposed antenna utilizes a meandered structure in order to achieve dual band properties as well as size miniaturization. The antenna is designed using the CST Microwave Studio full-wave simulator and various parameters are optimized in order to achieve maximum gain in both the bands. A prototype of the proposed antenna is fabricated and tested to validate the simulation results. The proposed antenna is integrated with a Villard voltage doubler circuit using an impedance matching network and the output voltage and efficiency are monitored. The overall design of the proposed RF harvesting circuit is carried out using the Agilent ADS and a maximum efficiency of 46.82 % is achieved.